2020
DOI: 10.5382/econgeo.4725
|View full text |Cite
|
Sign up to set email alerts
|

A Multistage Genetic Model for the Metamorphosed Mesoproterozoic Swartberg Base Metal Deposit, Aggeneys-Gamsberg Ore District, South Africa

Abstract: The polymetamorphosed Swartberg Cu-Pb-Zn-Ag deposit in the Namaqua Metamorphic Province of South Africa is a major metal producer in the region, yet its genesis remains poorly understood. The deposit comprises several stratiform to stratabound units, namely the Lower Orebody and Dark Quartzite, the overlying Barite Unit, and the Upper Orebody, all of which are folded by an F2 isoclinal syncline and refolded by an open F3 synform. A discordant Garnet Quartzite unit surrounds the Upper Orebody in the F2 hinge, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Independent support for supergene mobilization of base metals at a deposit scale can be derived from the base metal distribution at Black Mountain. There, both limbs of an Okiepian (1,210–1,180 Ma) F1 fold (Ryan et al., 1986) display a metal zonation from Cu‐rich (NNW) to Zn‐rich (SSE) (Cawood & Rozendaal, 2020). Stedman (1980) explained this by a hypothetical hydrothermal feeder zone that would have been fortuitously placed exactly in the position of the later fold hinge.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Independent support for supergene mobilization of base metals at a deposit scale can be derived from the base metal distribution at Black Mountain. There, both limbs of an Okiepian (1,210–1,180 Ma) F1 fold (Ryan et al., 1986) display a metal zonation from Cu‐rich (NNW) to Zn‐rich (SSE) (Cawood & Rozendaal, 2020). Stedman (1980) explained this by a hypothetical hydrothermal feeder zone that would have been fortuitously placed exactly in the position of the later fold hinge.…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…11). Rozendaal et al (2017) and Cawood and Rozendaal (2020) proposed that each deposit (except Broken Hill and its downplunge extension, Broken Hill Deeps) formed in a sub-basin of a larger extensional basin. Using the nomenclature of Ryan et al (1986), the Bushmanland Formation at Aggeneys consists of the Aluminous Schist Formation (~80 m thick) at its base that is composed of quartzmuscovite-K-feldspar-sillimanite-biotite rock.…”
Section: Aggeneys-gamsberg Ore District Namaqua Province South Africamentioning
confidence: 99%
“…Metamorphosed exhalative and/or premetamorphic alteration units in the Bushmanland Group include the iron formations, barite-bearing rocks, quartz-garnet rocks, nodular sillimanite rocks, and gahnite-bearing rocks (e.g., Spry, 1987b;Stalder and Rozendaal, 2004;Rozendaal et al, 2017). Quartz-garnet rocks occur in the stratigraphic footwall of the Broken Hill and Swartberg deposits and likely served as the alteration zones to ore (e.g., Stedman, 1980;Cawood and Rozendaal, 2020). Zones of barite ore occur at Gamsberg but they occur in significantly smaller amounts in the Aggeneys deposits; it is absent in the recently discovered Broken Hills Deep deposit.…”
Section: Aggeneys-gamsberg Ore District Namaqua Province South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…gahnite) cannot be explained easily by this genetic model. Furthermore, various geochemical anomalies in the immediate vicinity of the ore district (e.g., Willner et al 1990) and several studies, which point to inconsistencies in the redox conditions of the deposits (e.g., Stalder and Rozendaal 2005b;Cawood and Rozendaal 2020), all suggest a more complicated metallogeny. An oxidation event affecting the whole ore district between the Okiepian (1210( -1180 and Klondikean (1040-1020 Ma) orogenic events (Clifford et al 2004) has been suggested based on Cu isotope data (Höhn et al 2020).…”
Section: Introductionmentioning
confidence: 99%